Optical photometric variable stars towards Cygnus OB7. Issue 2 (20th May 2019) - Dutta, Somnath; Mondal, Soumen; Joshi, Santosh; Das, Ramkrishna
ABSTRACT: We present optical I -band light curves of the stars towards a star-forming region Cygnus OB7 from 17-night photometric observations. The light curves are generated from a total of 381 image frames with very good photometric precision. From the light curves of 1900 stars and their periodogram analyses, we detect 31 candidate variables including five previously identified. 14 out of 31 objects are periodic and exhibit the rotation rates in the range of 0.15–11.60 d. We characterize those candidate variables using optical/infrared colour–colour diagram and colour–magnitude diagram (CMD). From spectral indices of the candidate variables, it turns out that four are probably Classical T-Tauri stars (CTTSs), rest remain unclassified from present data, they are possibly field stars or discless pre-main-sequence stars towards the region. Based on their location on the various CMDs, the ages of two T Tauri Stars were estimated to be ∼5 Myr. The light curves indicate at least five of the periodic variables are eclipsing systems. The spatial distribution of young variable candidates on Planck 857 GHz (350 $μ$ m) and 2MASS (Two Micron All Sky Survey) K s images suggest that at least two of the CTTSs are part of the active star-forming cloud Lynds 1003.